All‐Solid‐State Flexible Ultrathin Micro‐Supercapacitors Based on Graphene. (29th May 2013) - Niu, Zhiqiang; Zhang, Li; Liu, Lili; Zhu, Bowen; Dong, Haibo; Chen, Xiaodong
<x xml:space="preserve">Abstract</x> Flexible, compact, ultrathin and all‐solid‐state micro‐supercapacitors are prepared by coating H3PO4/PVA gel electrolyte onto micro‐patterned rGO interdigitated electrodes prepared by combining photolithography with selective electrophoretic deposition. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>